2010
DOI: 10.4028/www.scientific.net/amr.121-122.878
|View full text |Cite
|
Sign up to set email alerts
|

Research on an Electro-Mechanical Hybrid Power Controller

Abstract: Electro-mechanical hybrid power controller (EMHPC) is a kind of switch with a breaker as mechanical switch and an insulated gate bipolar transistor (IGBT) as solid-state switch. It is a key element of electrical load management center (ELMC) of the more electric aircraft (MEA). On the condition of high voltage (270VDC) and large current (200A), the proposed EMHPC in this paper features great simplicity and reliability. It has no contact chatter when the controller is turned on or off, main circuit will be shut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The simulation results indicated fast transfer switching (in under microseconds) and greater overall protection, justifying the efficient operation of circuit breakers in the distribution system. Zhang et al [6] introduced an electro-mechanical hybrid power controller (EMPHC) utilizing insulated gate bipolar transistors (IGBT) and a mechanical switch. They suggested that EMHPC can be used for electrical control, isolation, and fault protection in aircraft systems.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation results indicated fast transfer switching (in under microseconds) and greater overall protection, justifying the efficient operation of circuit breakers in the distribution system. Zhang et al [6] introduced an electro-mechanical hybrid power controller (EMPHC) utilizing insulated gate bipolar transistors (IGBT) and a mechanical switch. They suggested that EMHPC can be used for electrical control, isolation, and fault protection in aircraft systems.…”
Section: Introductionmentioning
confidence: 99%